The Effect of Chronic High Dose Vitamin a Supplementation on Lipid Metabolism in Adipose Tissue (P02-013-19). (13th June 2019) - Finney, Kieran; Oxley, Anthony; Winder, Catherine; Southam, Andrew; Jankevics, Andris; Lloyd, Gavin; Giles, Tim; Foster, Neil; Dunn, Warwick; Lietz, Georg
Abstract: Objectives: The objective of this study was to assess the impact of high-dose vitamin A (VA) on lipid metabolism. Previously, VA has been shown to enhance fat mobilisation, leading to a reduction in body fat. We hypothesise that hypervitaminosis A will increase expression of genes associated with lipid catabolism. Methods: To induce chronic hypervitaminosis A, two groups of pigs ( n = 8) were fed a commercial diet. The treatment group was additionally dosed, daily, with an oral supplement of retinyl propionate of 10, 000 µg/KgBW for 17 weeks. To assess the impact of VA on lipid metabolism, a microarray analysis was performed to identify gene expression in adipose tissue. Differentially expressed transcripts and pathways were identified using Genespring and mapped to human orthologues for Ingenuity Pathway Analysis (IPA); gene fold changes were confirmed using qRT-PCR. Additionally, an untargeted UPLC-MS lipidomic analysis was carried out in serum samples to identify changes in lipd classes and their metabolites. Results: In dosed animals, significant increases in plasma retinol (0.66 μmol/L) and liver retinyl ester concentrations (11.98 μmol/g both P < 0.001), as well as an increase in serum NEFA of 92.84 μ mol/L ( P = 0.001) were observed. Gene expression fold changes in subcutaneous adipose tissue were related to mitochondrial dysfunction and lipid metabolism, including increased expression of MT-CYTB (↑4.78x, P < 0.05) and ATP5A1 (↑3.13x, P < 0.05). Metabolomics confirmed changes in lipids and their metabolites relevant to adipose tissue in blood ( P = 0.05), namely a decrease in triacylglyceride concentration and increases in acyl carnitine and cardiolipin concentrations. Conclusions: An integrated pathway is suggested to explain the role of vitamin A in leading to increased lipolysis, β-oxidation and oxidative phosphorylation, but when in excess, markers of mitochondrial dysfunction were observed. Funding Sources: Funded by the Bill and Melinda Gates foundation.